2021
DOI: 10.4081/oncol.2020.439
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and predictive accuracy of thyroglobulin to TSH ratio and TSH to thyroglobulin ratio in detecting differentiated thyroid carcinoma in normothyroid patients with thyroid nodules: A retrospective cohort study and systematic review of the literature

Abstract: The purpose of the present study is to examine the diagnostic and predictive accuracy of the thyroglobulin (Tg) to thyroid stimulating hormone (TSH) and TSH/Tg ratios in normothyroid patients with differentiated thyroid cancer (DTC). We conducted a retrospective cohort study evaluating the diagnostic accuracy of the serum Tg/TSH and TSH/Tg ratios in normothyroid patients with thyroid nodules. We also systematically searched the international literature using the Medline, Cochrane’s CENTRAL, Scopus, Clinicaltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Karvounis et al, [ 13 ] proposed that TG/TSH and/or TSH/TG ratios could be a marker of malignancy, with the hypothesis that malignant cells may respond differently to TSH than benign cells since TSH is a factor that directly affects the secretion of TG. In their study, they found that both TG/TSH and TSH/TG ratios differed significantly between malignant and BGs in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Karvounis et al, [ 13 ] proposed that TG/TSH and/or TSH/TG ratios could be a marker of malignancy, with the hypothesis that malignant cells may respond differently to TSH than benign cells since TSH is a factor that directly affects the secretion of TG. In their study, they found that both TG/TSH and TSH/TG ratios differed significantly between malignant and BGs in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…They determined the cutoff value for the TG/TSH ratio as 15.6 ng/mIU. [ 13 ] In our large series of 402 patients with DTC, we observed significant differences in the TG/TSH ratio (14.36 [0.04–13100.0] vs. 62.75 [0.09–3265.0], p≤0.001) and TSH/TG ratio (1.25 [0.000076–22.48] vs. 0.01 [0.0003–10.60], p≤0.001), and we demonstrated these results in the diagnostic ROC analysis (p≤0.001 for TG/TSH, p<0.001 for TSH/TG). In our study, the cutoff value for TG/TSH was determined as 29.67.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various attempts have been made to improve the specificity of the Tg measurement by linking it with other diagnostic param-eters. For example, the value of a TSH/Tg ratio or Tg/TSH ratio was examined [80][81][82][83]. Ultimately, however, such ratio cannot significantly improve the accuracy of diagnosing a DTC.…”
Section: Pre-operative Tg Measurementmentioning
confidence: 99%